Animating Difference: Race, Gender, and Sexuality in Contemporary Films for Children - King, C. Richard; Lugo-Lugo, Carmen R.; Bloodsworth-Lugo, Mary K. (Rowman & Littlefield Publishers, 2010)
Animating Difference studies the way race, ethnicity, sexuality, and gender are portrayed in recent animated films from 1990 through the present. Ranging from Aladdin to Toy Story to Up, these popular films are key media through which children (and adults) learn about the world and how to behave. While racial and gender stereotypes may not be as obvious as they may have been in films of decades past, they often continue to convey troubling messages and stereotypes in subtle and surprising ways.